A ética do cuidado de Hans Jonas no equacionamento da complexidade da responsabilização de danos futuros decorrentes da utilização de nanocosméticos - Jeckel, Lisiane Cristina Jeckel (Universidade do Vale do Rio dos Sinos, 2019)
The incursion of new techniques from technological advancement has enabled human beings to manipulate atomic level creating infinite possibilities in the most varied industries, including cosmetics. Faced with this situation, nanotechnology has been imperceptibly inserted into the cosmetic market by incorporating nano-scale elements into conventional cosmetics. While this technology enhances the performance and effectiveness of these products, the long-term health and environmental risks are unknown. The lack of specific regulation, as well as the lack of information to the consumer allow the nanocosmetics to be absorbed by the market without due concern. This scenario corresponds to the ethical proposal of Hans Jonas, the contemporary philosopher who was concerned with the risks arising from technological advancement, not only to humans but also to nature. Therefore, he sought to transpose the anthropocentrism that is present in traditional ethics. Concerned about the future, he believed on the heuristic of fear, through precaution, as a limiter of actions that may compromise human life in both present and future generations. Thus, the concern that arises and moves the research is: under what circumstances can the Jonas's caring ethics promote the informed consumption of nanocosmetics and the possible liability for future damages arising from this technology? By hypothesis we have the application of the principle of responsibility of Jonas throughout the life cycle of nanocosmetics, in other words, since its elaboration until the final disposal, allied to principles and norms present in Brazilian law that refer to the caring ethics. Therefore, this research aims to study the conditions that signal that Jonas's caring ethic can promote nanocosmetic consumer safety. To achieve the proposed objective, the bibliographic research was associated with Laurence Bardin's content analysis method. This research showed that the application of the Jonas´s Responsibility Principle, based on the precautionary principle and on the right to information, could be an important instrument for fostering conscious consumption of nanocosmetics, as well as for making society responsible for a present with managed risks, and perhaps a future without damage.
Keywords: Nanocosméticos; Riscos; Hans Jonas; Precaução; Direito à informação; Segurança do Consumidor; Nanocosmetics; Risks; Hans Jonas; Precaution; Right to information; Consumer Safety; ACCNPQ::Ciências Sociais Aplicadas::Direito